2011
DOI: 10.5194/angeo-29-1305-2011
|View full text |Cite
|
Sign up to set email alerts
|

IMF <i>B</i><sub><i>y</i></sub> effects in the plasma flow at the polar cap boundary

Abstract: Abstract. We used the dataset obtained from the EISCAT Svalbard Radar during [2000][2001][2002][2003][2004][2005][2006][2007][2008] to study statistically the ionospheric convection in a vicinity of the polar cap boundary as related to IMF B y conditions separately for northward and southward IMF. The effect of IMF B y is manifested in the intensity and direction of the azimuthal component of ionospheric flow. The most significant effect is observed on the day and night sides whereas on dawn and dusk the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One of the most important impact factors is the Y component of IMF. As the results of some previous studies, B Y can lead to an asymmetry of the two‐cell plasma convection pattern at the high‐latitude ionosphere [e.g., Heelis , ; Reiff and Burch , ; Heppner and Maynard , ], thereby the asymmetry of the OCB [e.g., Lee et al , ; Lukianova and Kozlovsky , ].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…One of the most important impact factors is the Y component of IMF. As the results of some previous studies, B Y can lead to an asymmetry of the two‐cell plasma convection pattern at the high‐latitude ionosphere [e.g., Heelis , ; Reiff and Burch , ; Heppner and Maynard , ], thereby the asymmetry of the OCB [e.g., Lee et al , ; Lukianova and Kozlovsky , ].…”
Section: Introductionmentioning
confidence: 57%
“…When the IMF has a positive(duskward) component in addition to the southward B Z , the reconnection sites at the dayside magnetopause move from the equator to higher latitude of Northern Hemisphere at duskside and Southern Hemisphere at dawnside [ Park et al , ]. This causes a dawnward plasma flow in polar cap, and the duskside cell becomes more dominant than the dawnside [e.g., Cowley et al , ; Lukianova and Kozlovsky , ], as shown in Figure b. The dawnward flow brings more open flux to dawnside; thus, the dawnside OCB has a lower latitude than duskside OCB at the Northern Hemisphere.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Since the upstream solar wind conditions have a major influence on the reconnection of magnetopause/magnetotail, its variations may lead to the dynamics of PCB. Especially, the Y component of IMF can cause an asymmetry of the two-cell plasma convection pattern at the high-latitude ionosphere (e.g., [3,4]), thereby the dawn-dusk asymmetry of cutoff latitudes for protons and electrons [5], and polar cap boundary (e.g., [6,7]). In many studies, the polar cap boundary and area were used as a diagnostic of magnetospheric activities specifically during a substorm cycle (e.g., [8][9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have increasingly focused on asymmetries in the coupled magnetosphere‐ionosphere system [e.g., Sandholt and Farrugia , 2007; Laundal et al , 2010; Shi et al , 2010; Grocott et al , 2010; Lukianova and Kozlovsky , 2011]. Such asymmetries are intrinsically linked to the mechanisms that drive the dynamics of the system and in order to fully understand these mechanisms the asymmetries they introduce must be fully understood.…”
Section: Introductionmentioning
confidence: 99%